2019
DOI: 10.4269/ajtmh.18-0927
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, Obesity, and Older Age Favor Latent Tuberculosis Infection among Household Contacts in Low Tuberculosis-Incidence Settings within Panama

Abstract: Latent tuberculosis infection (LTBI) remains the main source of new active tuberculosis (TB) cases worldwide. Household close contacts (HCCs) are at high risk of acquiring LTBI and subsequent development of TB. In this study, we aim to identify risk factors associated with LTBI in HCCs of TB patients living in a low TB-incidence setting. Our results revealed that HCCs who are aged more than 50 years (OR = 4.05) and overweight (OR = 15.3) are at higher risk of acquiring LTBI. None of these LTBI household contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
2
8
0
5
Order By: Relevance
“…found an association between a persistently TST negative result and a lower prevalence of lean mass wasting in the Uganda cohort. This is also in line with what some other studies have found ( 73 , 86 ). Verrall et al.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…found an association between a persistently TST negative result and a lower prevalence of lean mass wasting in the Uganda cohort. This is also in line with what some other studies have found ( 73 , 86 ). Verrall et al.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, Igo et al found an association between a persistently TST negative result and a lower prevalence of lean mass wasting in the Uganda cohort. This is also in line with what some other studies have found(73,86). Verrall et al highlighted important evidence that BCG-vaccination provides dose dependent protection against IGRA conversion in HHC…”
supporting
confidence: 87%
“…Several lines of evidence support an association between BMI and the development of LTBI. 12 - 20 Cardiometabolic risk markers associated with obesity—such as fasting insulin, total cholesterol, LDL-cholesterol, HDL-cholesterol, and fasting triglycerides—are all linked to increased prevalence of diabetes mellitus. 16 Diabetes increases the risk of both LTBI and TB and has been associated with adverse treatment outcomes, including death.…”
Section: Introductionmentioning
confidence: 99%
“… 14-16 In contrast, some evidence has emerged demonstrating that individuals who are overweight, in close contact with active TB patients and over 50 years of age are all at higher risk of LTBI compared to their counterparts of normal weight. 17 Furthermore, in a population-based study from rural China, overweight and obese subjects were shown to have higher rates of LTBI positivity compared to individuals with normal body weight. 18 …”
Section: Introductionmentioning
confidence: 98%